DESAIN DAN UJI COBA LEMBAR KERJA PESERTA DIDIK UNTUK MATERI SEL ELEKTROLISIS BERBASIS GUIDED INQUIRY DENGAN STRATEGI READING INFUSION - Nurul Hidayati; Yusbarina Yusbarina (Journal of Chemistry Education and Integration, 2023)
Abstract The lack of learning media at State Senior High School 1 Tempuling caused the twelfth-grade students got difficulty in understanding Electrolytic Cell concept.  So, this research aimed at designing learning media in the form of valid and practical Reading Infusion Strategy Guided Inquiry Based Student Worksheet on Electrolytic Cell lesson.  It was Research and Development (R&D) with ADDIE development model, but only 4 steps were used in this research, and they were analysis, design, development, and implementation.  Observation, interview, validity and practicality test questionnaires were the techniques of collecting data.  The subjects of this research were a material expert validator, a media expert validator, 2 Chemistry subject teachers, and 12 students.  The object was the appropriateness of Reading Infusion Strategy Guided Inquiry Based Student Worksheet media on Electrolytic Cell lesson.  The validation results by material and media expert of Reading Infusion Strategy Guided Inquiry Based Student Worksheet on Electrolytic Cell lesson continuously were 93.38% and 96.66% with very good category.  The teacher and student practicality percentage results continuously were 89.66% and 85.56% with very good category.  Based on these results, Reading Infusion Strategy Guided Inquiry Based Student Worksheet on Electrolytic Cell lesson was appropriate to be used as a teaching material. Keywords: Student Worksheet, Guided Inquiry, Reading Infusion, Electrolytic Cell